Toward an integrative account of social cognition: marrying theory of mind and interactionism to study the interplay of Type 1 and Type 2 processes - Bohl, Vivian; van den Bos, Wouter (Frontiers in Human Neuroscience, 2012)
Traditional theory of mind accounts of social cognition have been at the basis of most studies in the social cognitive neurosciences. However, in recent years, the need to go beyond traditional theory of mind accounts for understanding real life social interactions has become all the more pressing. At the same time it remains unclear whether alternative accounts, such as interactionism, can yield a sufficient description and explanation of social interactions. We argue that instead of considering theory of mind and interactionism as mutually exclusive opponents, they should be integrated into a more comprehensive account of social cognition. We draw on dual process models of social cognition that contrast two different types of social cognitive processing. The first type (labelled Type 1) refers to processes that are fast, efficient, stimulus-driven, and relatively inflexible. The second type (labelled Type 2) refers to processes that are relatively slow, cognitively laborious, flexible, and may involve conscious control. We argue that while interactionism captures aspects of social cognition mostly related to Type 1 processes, theory of mind is more focused on those based on Type 2 processes. We suggest that real life social interactions are rarely based on either Type 1 or Type 2 processes alone. On the contrary, we propose that in most cases both types of processes are simultaneously involved and that social behaviour may be sustained by the interplay between these two types of processes. Finally, we discuss how the new integrative framework can guide experimental research on social interaction.